PENGARUH MODUL DIGITAL BERBASIS CPS BERNUANSA ETNOMATEMATIKA TERHADAP HOTS SISWA KELAS VIII SMPN 8 PADANG - Afifah, Adzra (Departemen Matematika, 2024)
Students must develop High Order Thinking Skills (HOTS) in order to thrive in this era of rapid technological advancement and increased globalization. But the truth is that eighth graders at SMPN 8 Padang still have relatively low levels of higher-order thinking skills (HOTS) since their lessons aren't well-designed to foster their development. The problem of inadequate higher-order thinking skills (HOTS) can be effectively tackled by introducing a digital module that combines ethnomathematical aspects with creative problem-solving (CPS) strategies. This study set out to test the hypothesis that, when compared to more traditional forms of instruction, developing students' higher-order thinking abilities (HOTS) through the use of CPS-based digital modules that incorporate ethnomathematical subtleties yields better results. This study used a quasi-experimental methodology, more especially, a control group design with nonequivalent posttests. For this research, we will use data from two classes chosen at random from among all eighth graders at SMPN 8 Padang throughout the 2024–2025 school year. Two classes will be chosen at random; one will serve as the control group and the other as the experimental group. The final evaluation of the HOTS was used as the research tool. Students who used digital modules that combined creative learning (CPS) outperformed those who stuck to traditional teaching resources on the HOTS final exam when it came to higher-order thinking skills.Keywords– High Order Thinking Skill, Creative Problem Solving, Digital Modules, Ethnomathematics